Persona e famiglia nell'era del Biodiritto Verso un diritto comune europeo per la bioetica - Baldini, Gianni (Studi e saggi, 2015)
The unceasing change that science and technology have imposed on civil society brings into question fundamental issues such as birth, health, death, together with the 'legal instruments' designed for the self-determination. Not only the individual is affected by this tumultuous process but also the family institution, as the main place where the self exercises its personality. In this third volume of Verso un diritto europeo per la bioetica ("Towards a European bioethics law") the focus of the contributions by various authors (jurists, doctors, bioethicists) is centred on topics such as: responsible parenthood and artificial insemination, anticipatory profiles taken on by health and related protection needs, articulation of family models and redefinition of the parenting project. All of this is declined in the logic of Biolaw, which is an autonomous discipline but also an investigation and a working method for those who intend to approach the so-called biotechnological cases.